Exercise in ankylosing spondylitis: quality of life and cost/utility - Lopes, Sofia (2017)
The objective of this study is to assess the perception of QoL and the ratio cost/utility of a specific exercise program in patients with AS. Quasi-experimental study, performed in 28 individuals with AS, divided into group-based, home-based and group-control. All participants, except the group-control, did a specific exercise program to AS for 12 weeks. The evaluation was conducted in two stages, before (M0) and after (M1) the exercise program. Was utilized the Bath Indices, SF-36 and SF-6D as assessment instruments. The assumed significance value was 0.05. The experimental groups showed significant improvements in BASDAI and BASFI. There were significant differences among the three groups only in M1 BASMI (P = 0.035). It has been found in the SF-36, significant differences among groups M1 only. The results of the experimental groups of the SF-36, tended to increase, approaching the 100 (better QoL), this gains were more significant in group-based. The group-control showed significant results in BASDAI and BASFI, tending to worsen in all instruments. Regarding of cost/utility, for each 0.1 gain utility, cost/utility ratio for group-based was 211.90 € and home-based was 49.10 €. The performed exercise program was effective in producing changes in both experimental groups, being more evident in the group-based. The cost/utility ratio was more favourable in the home-based. The absence of physical exercise seems to negatively influence the course of the disease. Exercise has proven essential in the control/reduction in its symptoms and consequently the reduction in the indirect costs and increasing utilities.